Application of Capital Budgeting Method to Evaluate Investment Decisions on Additions to Fixed Assets at PT Hatten Bali - Ni Luh Gede Wahyu Pradnyawati; I M A Putrayasa; I G A O Sudiadnyani (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
This research was conducted to evaluate the investment decision to add fixed assets by PT Hatten Bali using the capital budgeting method. The results of this study are expected to be used as material for evaluating the application of the capital budgeting method in making investment decisions on fixed assets at PT Hatten Bali. The data used for this study were obtained from interviews and documentation and were analyzed using descriptive qualitative research analysis techniques with a case study approach. Based on the results of research using the capital budgeting method which consists of the method of calculating the payback period, net present value, profitability index, internal rate of return and average rate of return, all of which have shown a favorable results. From these results it can be concluded that the investment decision to add fixed assets in the form of distribution vehicles made by PT Hatten Bali can benefit the company in stable sales conditions and the application of capital budgeting methods can reduce the risk of errors or failures in making investment decisions and improve subsequent investment decisions.